Dimensionamento de reservatório para aproveitamento de água de chuva no município de Caçador/SC - Dapieve, Alan Roque (2014)
Being the lower reservoir (tank) the most expensive item of a collection and use of rain water system in a residence, this work is devoted to study and determine which of the calculation methods provided by Annex A of NBR 15527 (ABNT, 2007) appears more feasible to Caçador/SC reality, considering the use of the collected water for non-potable purposes in residential dwellings. For this analysis the reservoirs were calculated for 27 cases of hypothetical households, which varied the catchment area, the number of people of the building and the demand for nonpotable water. The calculations have been developed with the assistance of spreadsheets and for each of the 27 cases the volume of the reservoir were calculated by 6 (six) methods of the standard. After the calculated volumes simulated the behavior of each of the reservoirs, also through the spreadsheet, considering its behavior over a series of daily precipitation data with a duration of 20 years. It was considered the most appropriate method for Caçador who had the lowest volume eing empty for a maximum of 10% of the time, it is possible to determine the most interesting method for Caçador reality is the Practical Method Australian, excelling in 81,5% of the simulated cases.